2022
DOI: 10.1186/s12884-022-05007-0
|View full text |Cite
|
Sign up to set email alerts
|

Improved maternal–fetal outcomes among emergency obstetric referrals following phone call communication at a teaching hospital in south western Uganda: a quasi-experimental study

Abstract: Background Emergency obstetric referrals develop adverse maternal–fetal outcomes partly due to delays in offering appropriate care at referral hospitals especially in resource limited settings. Referral hospitals do not get prior communication of incoming referrals leading to inadequate preparedness and delays of care. Phone based innovations may bridge such communication challenges. We investigated effect of a phone call communication prior to referral of mothers in labour as i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 31 publications
2
12
0
Order By: Relevance
“…This was true as evidenced by the experimental study findings. The intervention reduced patient waiting time on the admission bench and we observed that there was less adverse maternal-fetal outcomes in the intervention group compared to the control group [9].…”
Section: Tions Open Journal Of Preventive Medicinementioning
confidence: 62%
See 2 more Smart Citations
“…This was true as evidenced by the experimental study findings. The intervention reduced patient waiting time on the admission bench and we observed that there was less adverse maternal-fetal outcomes in the intervention group compared to the control group [9].…”
Section: Tions Open Journal Of Preventive Medicinementioning
confidence: 62%
“…The control group was composed of emergency maternal referrals from a similar health centre IV (Kabuyanda HCIV) in the same district (Isingiro district) utilizing only the referral forms, which is the standard-of-care. No phone call was made for the referrals from the control group [9].…”
Section: The Context Of the Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet it is sometimes the most basic interventions, such as providing receiving hospital midwives with a mobile phone rather than paper transfer forms, that may show the most significant impact. In a study conducted in Uganda by Kanyesigye et al., 53 significantly fewer adverse maternal and fetal outcomes were found in a group that received mobile phone–based versus nonverbal handoff of care. Li et al 54 .…”
Section: Discussionmentioning
confidence: 92%
“…Women were surprised to receive respectful maternity care in the referral facility contrary to rumors of prevalent mistreatment in the referral hospital. The availability of functional CEMOC services and respectful maternity care boosts con dence in the referral facility and results in positive birth outcomes (5,11).…”
Section: Discussionmentioning
confidence: 99%